Proinflammatory cytokine interleukin-1β suppresses cold-induced thermogenesis in adipocytes. (January 2016) - Goto, Tsuyoshi; Naknukool, Supaporn; Yoshitake, Rieko; Hanafusa, Yuki; Tokiwa, Soshi; Li, Yongjia; Sakamoto, Tomoya; Nitta, Takahiro; Kim, Minji; Takahashi, Nobuyuki; Yu, Rina; Daiyasu, Hiromi; et al.
Highlights: IL-1β expression levels were enhanced in white adipose tissue from obese mice. IL-1β attenuated UCP1 induction via ERK activation in C3H10T1/2 adipocytes. IL-1β impaired β-adrenoreceptor-stimulated activation of the UCP1 promoter. IL-1β administration impaired cold-induced UCP1 upregulation in adipose tissues. Abstract: In this study, we investigated the effects of interleukin-1β (IL-1β), a typical proinflammatory cytokine on the β-adrenoreceptor-stimulated induction of uncoupling protein 1 (UCP1) expression in adipocytes. IL-1β mRNA expression levels were upregulated in white adipose tissues of obese mice and in RAW264.7 macrophages under conditions designed to mimic obese adipose tissue. Isoproterenol-stimulated induction of UCP1 mRNA expression was significantly inhibited in C3H10T1/2 adipocytes by conditioned medium from lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages in comparison with control conditioned medium. This inhibition was significantly attenuated in the presence of recombinant IL-1 receptor antagonist and IL-1β antibody, suggesting that activated macrophage-derived IL-1β is an important cytokine for inhibition of β-adrenoreceptor-stimulated UCP1 induction in adipocytes. IL-1β suppressed isoproterenol-induced UCP1 mRNA expression in C3H10T1/2 adipocytes, and this effect was partially but significantly abrogated by inhibition of extracellular signal-regulated kinase (ERK). IL-1β also suppressed the isoproterenol-induced activation of the UCP1 promoter and transcription factors binding to the cAMP response element. Moreover, intraperitoneal administration of IL-1β suppressed cold-induced UCP1 expression in adipose tissues. These findings suggest that IL-1β upregulated in obese adipose tissues suppresses β-adrenoreceptor-stimulated induction of UCP1 expression through ERK activation in adipocytes.